IMPACT OF COVID-19 PANDEMIC ON FOOD CONSUMPTION PATTERN IN THE POPULATION OF NAIROBI, KENYA - Mbijiwe, Jane; Kiiru, Samuel; Konyole, Silvenus; Ndung’u, Nancy; Kinyuru, John (Journal of Agriculture Science & Technology, 2021)
The COVID-19 pandemic has had an impact on food systems globally especially due to itscontainment measures and this has disrupted food consumption patterns among individuals. The study compared food consumption patterns and diet quality before and upon the onset of the COVID-19 pandemic in urban households in Nairobi City, Kenya. The investigationwas cross-sectional in nature with 1460 respondents, conducted between May-June 2020. The survey linkwas disseminated to respondents using online platforms namely WhatsApp, Twitter, Facebook and emails. A seven-day food frequency questionnaire was incorporated that sought what they consumed 7-days before and 7-days after the onset of the COVID-19 pandemic. Descriptive statistics and Chi-square tests were used to determine the association among variables. A 95% confidence interval was adopted. The respondents were 1460 in total, a majority (52.7%) being women with a mean age of 49 years, most (58%) were employed and 96% had a college/ university education. There was an increase in the intake of cereals from 62.3% to 72.6%, a decline in consumption of sugar from 42.5% to 30.8% and dairy products from 70.5% to 58.9% amid the COVID-19 pandemic. In addition, there was a rise in the intake of fruits and vegetables among respondents from 56.2% to 66.4% and a decrease in consumption of meat, poultry, fish, and eggs from 30.1% to 25.3% amid the covid-19 pandemic. This inquiry observed a significant association between intake of fats and oils with respondents’ occupation (p=0.011), income (p= 0.003) and age (p<0.001). The majority (67.1%) of the participants reported an improvement in food hygiene practices while intake of fresh foods deteriorated (50%). The study showed that the COVID-19 pandemic skewed consumption of healthy diets which may influence body immunity hence the ability to suppress SARS-CoV-2 infection.
Keywords: COVID-19 pandemic; Food consumption patterns; Diet quality; SARS-CoV-2